Sarthaks Test
+2 votes
1.8k views
in Mathematics by (128k points)
edited by
Show that tan3x tan2x tanx = tan3x – tan2x – tanx

1 Answer

+3 votes
by (65.0k points)
selected by
 
Best answer

Solution: We know that 3x = 2x + x
Therefore, tan 3x = tan (2x + x)
or


or tan 3x – tan 3x tan 2x tan x = tan 2x + tan x
or tan 3x – tan 2x – tan x = tan 3x tan 2x tan x
or tan 3x tan 2x tan x = tan 3x – tan 2x – tan x.

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...